2004
DOI: 10.1159/000077333
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Oral Mucosal Abnormalities in True Umbilical Cord Knots

Abstract: Objective: The pathogenesis and clinical significance of true umbilical cord knots remain controversial. Here, we tested the hypothesis of the presence of congenital oral mucosal changes in newborns with true umbilical cord knots. Study design: Seven consecutive infants with true umbilical cord knots and 50 gestational age- and sex-matched controls were enrolled. The proportion of oral frenulum abnormalities and the two-dimensional vascular network geometry [fractal dimension, D, at two scales: D(1–46), and D(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…De Felice et al [151] proved it for Ehlers-Danlos II/III syndrome. De Felice et al [152] reported an increased vascular complexity in neonates with true umbilical cord knots. Parrini et al [153] did it for infantile hypertrophic pyloric stenosis.…”
Section: Variousmentioning
confidence: 98%
“…De Felice et al [151] proved it for Ehlers-Danlos II/III syndrome. De Felice et al [152] reported an increased vascular complexity in neonates with true umbilical cord knots. Parrini et al [153] did it for infantile hypertrophic pyloric stenosis.…”
Section: Variousmentioning
confidence: 98%
“…To deal with this problem, we always rely on independent observations by experienced odontostomatologists and record the findings with standard, high resolution photographs. Although this line of research has yielded valuable observations in EDS II/III (6) and true umbilical cord knots (7), we do not consider it the most appropriate IHPS screening method. We hypothesized that the most likely reason for MF abnormalities observed in our IHPS population was a hitherto unrecognized underlying extracellular matrix (ECM) abnormality.…”
mentioning
confidence: 99%